Kewenangan Pengawasan oleh Kementerian Lingkungan Hidup dan Kehutanan Republik Indonesia Terhadap Izin Dumping Limbah Bahan Berbahaya dan Beracun di Wilayah Kabupaten Bekasi - Chandra Ferdiawan; Mohammad Fasyehhudin (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
Bekasi Regency is a city that has a lot of industrial companies, many of these industries make environmental problems a problem in the Bekasi Regency area, illegal dumping activities of Hazardous and Toxic Materials are rampantly carried out by companies that do not have a B3 waste dumping permit. These problems make supervision related to dumping permits in the Bekasi district area important. Therefore, this study discusses how the authority to supervise hazardous and toxic waste dumping permits by the Ministry of Environment and Forestry of the Republic of Indonesia in the Bekasi Regency area based on Government Regulation Number 22 of 2021, how are the obstacles faced by the Ministry of Environment and Forestry of the Republic of Indonesia in supervise the dumping of B3 waste in the Bekasi Regency area.The research method used is empirical juridical, namely research that sees the law as a rule in society to be obeyed, with descriptive analysis specifications based on an analysis of the authority to supervise B3 waste dumping in Bekasi Regency which is sourced from primary data through field research and primary legal materials, namely legislation. , books, legal science journals, as well as other library materials analyzed in an analytical juridical manner.The results of this study state that the implementation of supervision and law enforcement on hazardous and toxic waste dumping permits carried out based on Government Regulation No. 22 of 2021 carried out by the Ministry of Environment and Forestry is good but not very effective in carrying out direct supervision both regularly and incidentally and there are still a few obstacles in carrying out supervision in the Bekasi Regency area, namely there are still uncooperative companies to supervise business activities, therefore the ministry of environment and forestry is expected to carry out preventive law enforcement so that all business actors comply with applicable regulations.